Bibliometric study on three journals of electronic commerce. - Mao, Yanlan. (2011)
In this dissertation, the publication patterns of three electronic commerce journals, namely, the International Journal of Electronic Commerce (IJEC), Electronic Commerce Research and Applications (ECRA), and the Journal of Organizational Computing and Electronic Commerce (JOCEC) were studied. Five years of bibliometric information, from 2004 to 2008, were retrieved from the Web of Science database, and to ensure accuracy, the records were counter-checked with those the ScienceDirect database. They were then analysed using the Microsoft Excel spreadsheet.